1997
DOI: 10.1074/jbc.272.50.31553
|View full text |Cite
|
Sign up to set email alerts
|

Probing the G-protein Regulation of GIRK1 and GIRK4, the Two Subunits of the KACh Channel, Using Functional Homomeric Mutants

Abstract: In heart, G-protein-activated channels are complexes of two homologous proteins, GIRK1 and GIRK4. Expression of either protein alone results in barely active or non-active channels, making it difficult to assess the individual contribution of each subunit to the channel complex. The residue Phe 137 , located within the H5 region of GIRK1, is critical to the synergy between GIRK1 and GIRK4 (Chan, K. W., Sui, J. L., Vivaudou, M., and Logothetis, D. E. (1996) Proc. Natl. Acad. Sci. U. S. A. 93, 14193-14198). By m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(156 citation statements)
references
References 34 publications
7
144
1
Order By: Relevance
“…We tested the effect of oleoylCoA on several other members of the Kir channel family, which were as follows: Kir1.1, Kir2.2, Kir2.3, Kir4.1, Kir4.2, and Kir3.4* (the homomerically active GIRK4 mutant S143T; ref. 30). We found that none of these channels was activated by 10 M oleoyl-CoA (data not shown).…”
Section: Resultsmentioning
confidence: 80%
“…We tested the effect of oleoylCoA on several other members of the Kir channel family, which were as follows: Kir1.1, Kir2.2, Kir2.3, Kir4.1, Kir4.2, and Kir3.4* (the homomerically active GIRK4 mutant S143T; ref. 30). We found that none of these channels was activated by 10 M oleoyl-CoA (data not shown).…”
Section: Resultsmentioning
confidence: 80%
“…Here, we use GIRK4(S143T) (denoted as GIRK4*), a homomeric-active GIRK4 channel with a mutation in the porehelix (11), to test the effectiveness of these G␤␥ mutants to enhance basal currents. We have previously shown that homomeric GIRK4* channels behave similarly to the GIRK1/GIRK4 heteromers and are therefore functionally interchangeable (15). Fig.…”
Section: G␤ Mutants Confer Functional But Not Binding Defects-wementioning
confidence: 99%
“…Deactivation kinetics were compared for Kir3.4(S143T) (a variant able to form functional homomers as described) (20) and Kir3.4(S143T/Y32F/Y53F) (a homomeric channel with both N-terminal tyrosine residues point-mutated to phenylalanines) (7). trkB activation accelerated channel deactivation in oocytes expressing Kir3.4(S143T) (vehicle, off ϭ 26 Ϯ 4 s, n ϭ 18 and BDNF, off ϭ 17 Ϯ 1 s, n ϭ 17).…”
Section: Fig 1 Trkb Accelerates Kir3 Deactivationmentioning
confidence: 99%